Embedding Party Organization Governance in Energy Management: Effects on Corporate Carbon Emissions in Chinese State-Owned Enterprises - Shiquan Wang; Yu Liang (Energies)
Theoretical and practical ambiguities concerning the impact of Party organization governance on corporate carbon emissions in China are addressed in this study. Data from A-share-listed state-owned enterprises in Shanghai and Shenzhen (2016–2021) are analyzed to determine how Party organization governance influences corporate carbon emissions. Fixed-effects regression results indicate that Party organization governance significantly reduces emissions. Robustness is established via alternative variable measures, instrumental variable estimation, and the inclusion of supplementary controls. Notably, the effect weakens as privatization intensifies. Conversely, SOEs embedding high-quality Party building into articles of association or situated in regions rich in red cultural resources exhibit amplified emission reductions. The findings enhance comprehension of Party organization governance’s environmental role in SOEs and inform the design of low-carbon energy governance frameworks.